2011
DOI: 10.1177/0892705711412646
|View full text |Cite
|
Sign up to set email alerts
|

Multiple extrusion and dilution of nanocomposites and their effect on the mechanical properties

Abstract: Commercially available TiO 2 and BaSO 4 nanoparticles were incorporated in polyamide 6 (PA 6) via twin screw extrusion. The primary particle size of these two nanoparticles was 15 nm and 20 nm, respectively. The compounds were manufactured via multiple extrusion and dilution processing steps. The dispersion of the nanoparticles in the matrix was investigated by scanning electron microscopy and image analysis. The mechanical properties were determined via tensile and bending tests. The toughness was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Figure 14 shows the state of the art of agglomerates after 8 times of extrusion, the so called dilution steps, to realize the final particle content. Even here we see remaining agglomerates which might be the reason for a lower impact strength in case of reinforced PA 6 25. For the 7 vol % masterbatch after two extrusion steps, analyzed rheologically, a dispersion index of D = 0.88 according to eq.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Figure 14 shows the state of the art of agglomerates after 8 times of extrusion, the so called dilution steps, to realize the final particle content. Even here we see remaining agglomerates which might be the reason for a lower impact strength in case of reinforced PA 6 25. For the 7 vol % masterbatch after two extrusion steps, analyzed rheologically, a dispersion index of D = 0.88 according to eq.…”
Section: Resultsmentioning
confidence: 83%
“…The viscosity is more increased by TiO 2 than for BaSO 4 . The interaction of TiO 2 with matrix is bigger than in case of BaSO 4 . This can be seen in a smaller slope for TiO 2 especially for G ′ in the lower frequency region. The remaining agglomerates seem to act as defects decreasing the energy absorption of the compound 25 A particle–particle network depended on particle loading and agglomeration can be found.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The nanoparticles are highly agglomerated in the powdery form and the agglomerates cannot be deagglomerated sufficiently in the kneading process. Literature has shown that nanoparticle powders deagglomerate insufficiently via extrusion processes …”
Section: Resultsmentioning
confidence: 99%
“…The properties of the nanocomposites are mainly dependent on a loading, the type and the dispersion state of the nanofillers within the polymer matrix and the polymer/ particle interphase (Lehmann et al, 2008;Knör et al, 2008;Hassinger and Burkhart, 2011;Ma et al, 2005;Lee and Goettler, 2004;Wu et al, 2005;Rong et al, 2001;Chen et al, 2008). However, microscale aggregates or agglomerates are often observed in nanoparticle-filled polymers.…”
Section: Introductionmentioning
confidence: 99%